Effectiveness of nevirapine and zidovudine in a pilot program for the prevention of mother-to-child transmission of HIV-1 in Uganda - Bajunirwe, Francis; Massaquoi, Iyesatta; Asiimwe, Stephen; Kamya, Moses R.; Arts, Eric J.; Whalen, Christopher C. (African Health Sciences, 2004)
Background: Single dose nevirapine and a short course of zidovudine (AZT) are now administered in most hospitals in Uganda to prevent mother-to-child transmission (MTCT) of HIV. The effectiveness of these antiretroviral (ARV) regimens has been shown in the clinical trials but has not been demonstrated outside the clinical trials setting in this country. Objectives: The study evaluated the effectiveness of short course ARV regimens in a pilot program to prevent mother-to child transmission of HIV and determined the risk factors for perinatal transmission. Methods: Cross-sectional study design was used to compare perinatal transmission rates of HIV in two sets of mothers: ARV-treated mothers and ARV-untreated mothers. Results: 109 treated and 90 naïve mother-infant pairs were recruited. HIV transmission rates were similar in the nevirapine (10/61) and AZT (8/48) groups (16.4% vs. 16.7%) respectively but higher in the naïve group (43/90 48%, p= 0.0001). ARV therapy offers a protective effect against MTCT of HIV (Adjusted Odds Ratio 0.22 95%CI 0.09, 0.54) but mothers in Stage 1 and 2 of disease were more likely to benefit from this intervention than mothers in Stage 3 and 4. Conclusion: In this community-based observational study, ARV reduces the risk of perinatal transmission of HIV but does not eliminate the risk completely. Early screening of asymptomatic pregnant women will identify a group of mothers more likely to benefit from the intervention
Keywords: HIV-1; Mother; Child; Transmission; Antiretroviral therapy